2009
DOI: 10.1371/journal.pone.0008006
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an Odorant-Binding Protein from the Mosquito Aedes aegypti Suggests a Binding Pocket Covered by a pH-Sensitive “Lid”

Abstract: BackgroundThe yellow fever mosquito, Aedes aegypti, is the primary vector for the viruses that cause yellow fever, mostly in tropical regions of Africa and in parts of South America, and human dengue, which infects 100 million people yearly in the tropics and subtropics. A better understanding of the structural biology of olfactory proteins may pave the way for the development of environmentally-friendly mosquito attractants and repellents, which may ultimately contribute to reduction of mosquito biting and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 40 publications
8
115
0
5
Order By: Relevance
“…3). It has been previously observed in the structures of AgamOBP1 and AaegOBP1 that the C-terminal carboxylate group interacts with the hydroxyl of Tyr54 and the δ-nitrogen of His23, making a potential pH-sensing triad that locks the C terminus onto helix 1 and helix 3 (25). We found that the same interaction is well conserved in the structure of the CquiOBP1·MOP complex.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…3). It has been previously observed in the structures of AgamOBP1 and AaegOBP1 that the C-terminal carboxylate group interacts with the hydroxyl of Tyr54 and the δ-nitrogen of His23, making a potential pH-sensing triad that locks the C terminus onto helix 1 and helix 3 (25). We found that the same interaction is well conserved in the structure of the CquiOBP1·MOP complex.…”
Section: Resultssupporting
confidence: 72%
“…Because helices 4 and 5 also form the dimeric interface of the crystal structure, the two MOP-binding tunnels of each CquiOBP1 dimeric unit meet and connect at the dimer interface. Notably, the same ligand-binding pocket was serendipitously identified in the previous structures of AgamOBP1 and AaegOBP1 by a bound PEG molecule from the crystallization solution (25,26). In those structures, a single PEG molecule 55-80 atoms long gets into one OBP molecule from an opening created by helices 1, 3, and 4; runs through the central cavities and the connected hydrophobic tunnels between helices 4 and 5; and comes out through the second OBP molecule of the dimer (Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Before this work, only the ortholog of Orco (153) and a small number of OBPs (154, 155) had been identified. The crystal structure of AaegOPB1 has been solved (156), and the odorant binding profile of AaegOBP22 has been characterized (157). However, the contribution that these OBPs make to odorant reception in vivo has not been determined.…”
Section: Quinquefasciatus: a Vector Of Filariasismentioning
confidence: 99%
“…Their affinities for ligands are also pH-dependent (Wogulis et al, 2006;Leite et al, 2009;Mao et al, 2010), whereas a C-terminal loop lacks a C-terminus region, which is also identical to Lma PBP with a direct end after the sixth helix in Leucophaea maderae (Lartigue et al, 2003) comparing with moth OBPs, folding into an extra α-helix at low pH. Hydrogen bonds involving the C-terminal loop, which forms part of the binding pocket, will be broken at low pH and make the loop open, releasing further ligands.…”
Section: The Three-dimensional (3-d) Structure Of Obpsmentioning
confidence: 99%